2004
DOI: 10.1128/iai.72.1.598-601.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Candida albicans Virulence during Experimental Hematogenously Disseminated Infection and Endothelial Cell Damage In Vitro

Abstract: Candida albicans must penetrate the endothelial cell lining of the vasculature to invade the deep tissues during a hematogenously disseminated infection. We compared 27 C. albicans mutants with their wild-type parent for their capacity to damage endothelial cells in vitro and cause a lethal infection in mice following tail vein inoculation. Of 10 mutants with significantly impaired capacity to damage endothelial cells, all had attenuated virulence. Therefore, the endothelial cell damage assay can be used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 36 publications
5
92
1
Order By: Relevance
“…24,25 Our affected patients showed clinical presentations similar to those previously described in the literature: some patients have an abrupt onset with hypovolemic shock requiring emergency surgery, while others have a more indolent course with fever or worsening renal function and imaging techniques revealing structural arterial lesions. 6e9, 21,22 The long evolution period could be considered important to allograft salvage, even though Bracale et al have reported disappointing outcomes: from 6 patients with large anastomotic pseudoaneurysm, 5 had open repair and 1 stent grafting.…”
Section: 10e19supporting
confidence: 77%
“…24,25 Our affected patients showed clinical presentations similar to those previously described in the literature: some patients have an abrupt onset with hypovolemic shock requiring emergency surgery, while others have a more indolent course with fever or worsening renal function and imaging techniques revealing structural arterial lesions. 6e9, 21,22 The long evolution period could be considered important to allograft salvage, even though Bracale et al have reported disappointing outcomes: from 6 patients with large anastomotic pseudoaneurysm, 5 had open repair and 1 stent grafting.…”
Section: 10e19supporting
confidence: 77%
“…C. albicans must invade oral epithelial cells and endothelial cells in order to damage these cells in vitro (15,43). Moreover, C. albicans mutants with impaired capacity to invade and damage host cells in vitro frequently have attenuated virulence in murine models of oropharyngeal and hematogenously disseminated candidiasis (12,39,43,51,61). These data suggest that the capacity of C. albicans to invade and damage host cells is an important virulence attribute.…”
Section: Als3 Functionmentioning
confidence: 99%
“…During HDC, this organism invades endothelial cells in order to escape from the vasculature and infect the deep tissues. The observation that invasion-defective C. albicans mutants display attenuated virulence in murine models of OPC and HDC is evidence of the critical importance of invasion to virulence (Phan et al 2000;Sanchez et al 2004;Park et al 2005;Chiang et al 2007). Invasion into both cell types occurs in part by endocytosis, which is induced when the C. albicans invasins Als3p and Ssa1p interact with receptors expressed on the surface of endothelial and epithelial cells (Phan et al 2007;Sun et al 2010).…”
mentioning
confidence: 99%